CARACTERIZAÇÃO DO COMPÓSITO METÁLICO DE TUNGSTÊNIO, USANDO LIGNINAS EXTRAÍDA DA MADEIRA DE EUCALIPTO - FERNANDES, Hedielle Brasil; DE SOUZA, Armando Cirilo; GOUVÊA, Adriana de Fátima Gomes; DA SILVA, Aline Cardos; DE SOUZA, Vinicius N. Alecrim (ANAIS DO ENIC, 2018)
-